Synergistic Effects of Lightning Activity and Other Disturbance Factors on NO2 in Yunnan and Its Surrounding Areas - ZHAO Pingwei; LI Liyin; WANG Jiani; REN Juzhang; CHEN Jing; ZHANG Yunqiu (Qixiang keji)
NO2 is the common precursor of the secondary conversion of PM2.5 and O3. Understanding its change characteristics and influencing factors is of great significance for the collaborative treatment of PM2.5 and O3. Based on the VLF/LF three-dimensional lightning location monitoring system, SNPP/VIIRS satellite fire point data, NO2 column density in Sentinel-5P NRTI NO2 data products and other data, using various statistical methods, selecting February to April with high NO2 density and June to August with frequent lightning activities, this paper compares and analyses the influence of lightning activities on NO2 density in region A (96.5°-102°E, 20.5°-24°N) with high biomass burning in southwest Yunnan and its surrounding areas and region B (102°-104°E, 24°-26°N) with high human activities in central Yunnan. The results show that: (1) There are obvious differences in the spatial and temporal distribution of the number of lightning and NO2 column density in region A and region B. The NO2 column density outside area A is higher than that in China, but the distribution of lightning times is the opposite. The NO2 column density in region B decreases from Kunming to the surrounding area, and the number of lightning is less and more. In the dry season (November to April of the next year), the concentration of NO2 density is higher, and the rainy season (May to October) is lower, and the number of lightning is opposite. (2) From February to April, the NO2 column density in region A and region B has a significant positive spatial correlation with the number of fire points and anthropogenic CO2 emissions, respectively, but a significant negative correlation with the number of lightning. (3) Lightning activity is mostly accompanied by obvious rainfall (R≥1 mm). When the lightning activity is weak, the wet deposition effect of rainfall on the ground NO2 density is obvious, and the wet deposition effect of rain falling from the stronger lightning activity cannot completely offset the contribution of lightning to the increase of ground NO2 density. (4) The change of surface NO2 density during the first lightning from June to August is more regular than that from February to April, which shows that the ground NO2 density increases hourly in the first 6 hours and decreases slowly hourly in the last 3 hours. (5) The ground NO2 density on the lightning days in the two regions is generally higher than those on the days without lightning. Changes in biomass combustion intensity, rainfall intensity and planetary boundary layer height have a significant impact on the ground NO2 density.